2001
DOI: 10.1074/jbc.m100576200
|View full text |Cite
|
Sign up to set email alerts
|

Unique Disulfide Bond Structures Found in ST8Sia IV Polysialyltransferase Are Required for Its Activity

Abstract: NCAM polysialylation plays a critical role in neuronal development and regeneration. Polysialylation of the neural cell adhesion molecule (NCAM) is catalyzed by two polysialyltransferases, ST8Sia II (STX) and ST8Sia IV (PST), which contain sialylmotifs L and S conserved in all members of the sialyltransferases. The members of the ST8Sia gene family, including ST8Sia II and ST8Sia IV are unique in having three cysteines in sialylmotif L, one cysteine in sialylmotif S, and one cysteine at the COOH terminus. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 56 publications
3
26
2
Order By: Relevance
“…Mutation of the two conserved cysteines yielded inactive enzymes (8 -10) and recent data suggest that they participate in the formation of an intramolecular disulfide linkage that is essential for maintaining an active conformation of the enzyme (11). Similar observations were made with the polysialyltransferase ST8Sia IV (12). In the latter case, a second intramolecular disulfide bond, which brings the sialylmotifs and the C terminus within proximity, has been evidenced.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Mutation of the two conserved cysteines yielded inactive enzymes (8 -10) and recent data suggest that they participate in the formation of an intramolecular disulfide linkage that is essential for maintaining an active conformation of the enzyme (11). Similar observations were made with the polysialyltransferase ST8Sia IV (12). In the latter case, a second intramolecular disulfide bond, which brings the sialylmotifs and the C terminus within proximity, has been evidenced.…”
supporting
confidence: 62%
“…However, we cannot rule out the possibility that residues upstream of sialylmotif L (motif 1) could be involved in acceptor recognition (or modulate the acceptor specificity) as suggested in previous studies (5). Recent data indicated the presence of an intramolecular disulfide bridge connecting the two conserved cysteine of motifs 1 and 2 (11,12). Whether the occurrence of disulfide bridge is a common feature to all STs remains to be established, but this would bring in close proximity sialylmotifs L and S and possibly residues at the N terminus of the catalytic domain near the catalytic center.…”
Section: Discussionmentioning
confidence: 99%
“…3 Interestingly, the disulfide linkage formed between Cys 59 and Cys 413 brings the amino acid residues located near the N and C termini of the catalytic domain within close proximity. This distinctive arrangement is similar to that occurring in ␣(1,3/1,4) fucosyltransferase III (51) and polysialyltransferase ST8Sia IV (52), where site-directed mutagenesis demonstrated that such steric conformation may be associated with acceptor substrate specificity (53,54) and catalytic efficiency (52), respectively. Similarly, the catalytic activity of GM2 synthase depends on the formation of disulfide-bonded homodimers, whose antiparallel orientation also brings the N and C termini in close proximity, most likely to establish a catalytic domain (55).…”
Section: Discussionmentioning
confidence: 78%
“…2ϩ . These fragments were generated from preferential cleavage of the amide bonds of Pro 52 and Pro 408 , respectively, and correspond to those predicted to occur in Pro-containing peptides, as indicated in studies reported previously (41). Frag- FIG.…”
Section: Identification Of Intramolecular Disulfidementioning
confidence: 99%
“…A polysialyltransferase domain (PSTD), located immediately upstream of SM-L in polysialyltransferases, is obligatorily required for polysialylation of target molecules (Nakata et al, 2006). The catalytic activity of STs depends on the formation of two disulfide bonds, through which these motifs are arranged in close proximity of each other (Angata et al, 2001; reviewed in Harduin- Lepers et al, 2005;Patel andBalaji, 2006, Nakata et al, 2006).…”
Section: Introductionmentioning
confidence: 99%